Elevational variation in body size of Crested Ducks (Lophonetta specularioides) from the central High Andes, Mendoza, and Patagonia - Bulgarella, Mariana (2007)
The Crested Duck (Lophonetta specularioides) inhabits the Andes of South America from Tierra del Fuego to central Perú, with two subspecies (L. s. specularioides and L. s. alticola) inhabiting different ele- vational environments in the Andes from sea level to 5000 m. We evaluated morphological differences between the two subspecies of Crested Duck and evidence for Bergmann?s and Allen?s rules to gain a bet- ter understanding of the forces that have acted to shape geographic variation in morphology of highland and lowland populations. Overall body size of Crested Ducks differed between subspecies and between sexes. Male and female L. s. alticola from the central high Andes sampled at 3338?4611 m were larger than L. s. specularioides from southern Patagonia (< 934 m to sea level). L. s. alticola individuals of intermediate body size were found at mid elevations (1522?2552 m) in Mendoza, Argentina. Stepwise discriminant anal- ysis (DA) classified 96.1% of L. s. alticola and 100% of L. s. specularioides males correctly; 100% of females were classified correctly. Body mass, wing chord, tarsus length, and bill length were positively correlated with elevation in male L. s. alticola, whereas total tarsus was negatively correlated with elevation in male L. s. specularioides. Crested Ducks conform to Bergmann?s Rule. No evidence was found for Allen?s Rule. Inter- mediate size Crested Ducks, such as those found in Mendoza, Argentina, might result from introgression between L. s. alticola and L. s. specularioides, and/or natural selection on body size of individuals locally adapted to intermediate elevational habitats.